Repurposing blue laser autofluorescence to measure ocular sun exposure. (14th November 2018) - Lingham, Gareth; Burton, Alex; Brown, Holly A.; Huynh, Emily; Yazar, Seyhan; Coroneo, Minas T.; Mackey, David A.
Abstract : Importance: Excessive ocular sun exposure is linked to various eye pathologies. Conjunctival ultraviolet autofluorescence (CUVAF) is a method of detecting sun‐related conjunctival damage; however, the custom‐built camera system required is not readily available. Background: We investigated whether blue laser autofluorescence (BAF) on a commonly used confocal scanning laser ophthalmoscope (cSLO) can be utilized to measure CUVAF area. Design: Cross‐sectional evaluation of a diagnostic technology at a medical research institute. Participants: Sixty‐four participants recruited from three on‐going observational eye studies in Western Australia. Methods: All participants had four images, two of each eye, captured using the CUVAF camera and BAF on the same day. Participants with pterygium or poor quality images were excluded from the analysis. Two graders measured CUVAF area in each image twice. CUVAF area measured by BAF was then compared to measurements determined with the conventional camera system. Main Outcome Measures: CUVAF area. Results: After exclusions, 50 participants' images were analysed. Intra‐ and inter‐observer repeatability were similar between the two systems. When comparing CUVAF area measured by BAF to the camera measurement, grader 1 had a mean difference of +1.00 mm 2, with 95% limits of agreement −5.75 to 7.77 mm 2 . Grader 2 had a mean difference of +0.21mm 2, with 95% limits of agreement −7.22 to 7.64 mm 2 . Conclusions and Relevance: BAF on a commercially available cSLO is a valid method for measuring CUVAF area. This finding provides broader opportunity for identifying, monitoring and educating patients with sun‐exposure‐related ocular conditions and for researching the ocular impacts of sun exposure.